Evidence-Based Guidelines for Management of Diabetic Macular Edema. (May 2019) - Bakri, Sophie J.; Wolfe, Jeremy D.; Regillo, Carl D.; Flynn, Harry W.; Wykoff, Charles C.
Purpose: The purpose of this article is to provide a data-driven set of best practices to consider in the management of diabetic macular edema (DME). Methods: The current discussion and recommendations represent the authors' interpretations of data from selected references based on perceived relevance and study design. Results: DME is a common cause of visual impairment globally. The underlying progressive retinal microvascular damage is associated with upregulation of VEGF and a multitude of other inflammatory pathways. Three clinically relevant subcategories of DME can be identified: central-involved DME (CIDME) with preserved visual acuity, CIDME with associated visual loss, and non-CIDME. Management approaches may include observation, laser photocoagulation, intravitreal pharmacotherapy with anti-VEGF agents or corticosteroids, or a combination of these, and may vary depending on the specific type of DME and associated severity of diabetic retinopathy. Additional factors to consider in the management of patients with DME include the appropriate use of imaging and recognition of the chronic nature of the underlying disease process in many eyes. Conclusions: DME management is complex. Intravitreal pharmacotherapies are the current cornerstone of treatment for CIDME and appear poised to remain so for the foreseeable future.